TACE-HAlC combined with Donafenib and immune checkpoint inhibitors for BCLC stage C HCC patients (THEME study): a retrospective IPTW-adjusted cohort study - Yin, Linan; Li, Weihang; Shao, Wencheng; Hou, Xunbo; Liu, Bowen; Liu, Xuesong; Liu, Ruibao; Huang, Peng (Frontiers in Immunology, 2025)
BackgroundTreatment options for Barcelona Clinic Liver Cancer (BCLC) Stage C hepatocellular carcinoma (HCC) remain limited, with targeted therapy combined with immune checkpoint inhibitors (ICIs) serving as the standard first-line treatment. This study investigates whether a combination of transarterial chemoembolization (TACE), hepatic arterial infusion chemotherapy (HAIC), donafenib, and ICIs (quadruple therapy) provides superior survival benefits compared to the targeted therapy combined with ICIs (targeted-immunotherapy).MethodsWe conducted a retrospective analysis of patients with BCLC stage C HCC who received quadruple therapy or targeted-immunotherapy at the Harbin Medical University Cancer Hospital between September 2019 and October 2024The primary outcome was overall survival (OS). Secondary outcomes included progression-free survival (PFS), objective response rate (ORR), Disease Control Rate (DCR) and safety. To minimize baseline imbalances between the groups, we applied stabilized inverse probability of treatment weighting (sIPTW) methods.ResultsA total of 195 patients were included in the study, of whom 125 were assigned to the quadruple therapy group and 70 to the targeted-immunotherapy Group. After applying sIPTW to balance the baseline characteristics between the two groups, patients in the quadruple therapy group demonstrated a significantly higher median OS (mOS) compared with the targeted-immunotherapy group (29.4 months [95% CI: 23.9-NA] vs 18.0 months [14.7-31.8]; P = 0.041). Additionally, the median PFS (mPFS) assessed by the modified Response Evaluation Criteria in Solid Tumors (mRECIST) was longer in the quadruple therapy group(16.4 months [95% CI: 12.7-NA] vs 10.0 months [3.32-31.8]; P = 0.012). Under the mRECIST criteria, quadruple therapy group demonstrated superior)ORR (68.4% vs 28.%, P = 0.001) and DCR (92.3% vs 63.1%, P < 0.001). The incidence of any adverse events (AE) in the quadruple therapy group was 95.2%, compared with 97.1% in the targeted-immunotherapy group. Among these the incidence of grade ≥3 AE was 40.8% in the quadruple therapy group and 38.6% in the targeted-immunotherapy group.ConclusionsCompared with targeted-immunotherapy group, patients with BCLC stage C HCC treated with TACE-HAIC combined with donafenib and ICIs demonstrated superior efficacy and acceptable safety.